The Effect of Positive Psychology on Human Flourishing Among Adolescent Students in The University of Buea - Busi Ernest Neba (Sean Institute, 2025)
This study aimed at investigating the effect of Positive Psychology on Human flourishing among Adolescents in the University of Buea with the following indicators, positive emotions, positive mental health, accomplishment and mindfulness. The study made used of a descriptive survey research design with a sample size of 200 adolescent students from the University of Buea. Questionnaire was to collect the data for the study. The descriptive statistics was used to analyze the data collected from respondents done and presented with the use of simple percentages, tables and figures. The findings of this study revealed that positive emotions positively affect students flourishing in the University Buea. Findings equally unveiled that positive mental health positively affect students flourishing in the University Buea. Findings also showed that being mindful positively affect students flourishing in the University Buea. Lastly, findings revealed that accomplishments positively affect students flourishing in the University Buea. Based on the findings, it was concluded the application of positive psychology positively affect human flourishing in the University of Buea. Based on the findings, it was recommended that administration and counseling professionals to look for ways of prevention and intervention to address low flourishing in university.